Hearing loss, hearing aid use, and subjective memory complaints: Results of the HUNT study in Norway - Moradi, Shahram; Engdahl, Bo; Johannessen, Aud; Selbæk, Geir; Aarhus, Lisa; Haanes, Gro Gade (Frontiers in Neurology, 2023)
Objective This study aimed to explore the association between hearing loss severity, hearing aid use, and subjective memory complaints in a large cross-sectional study in Norway. Methods Data were drawn from the fourth wave of the Trøndelag Health Study (HUNT4 Hearing, 2017–2019). The hearing threshold was defined as the pure-tone average of 0.5, 1, 2, and 4 kHz in the better ear. The participants were divided into five groups: normal hearing or slight/mild/moderate/severe hearing loss. Subjective self-reported short-term and long-term memory complaints were measured by the nine-item Meta-Memory Questionnaire (MMQ). The sample included 20,092 individuals (11,675 women, mean age 58.3 years) who completed both hearing and MMQ tasks. A multivariate analysis of variance (adjusted for covariates of age, sex, education, and health cofounders) was used to evaluate the association between hearing status and hearing aid use (in the hearing-impaired groups) and long-term and short-term subjective memory complaints. Results A multivariate analysis of variance, followed by univariate ANOVA and pairwise comparisons, showed that hearing loss was associated only with more long-term subjective memory complaints and not with short-term subjective memory complaints. In the hearing-impaired groups, the univariate main effect of hearing aid use was only observed for subjective long-term memory complaints and not for subjective short-term memory complaints. Similarly, the univariate interaction of hearing aid use and hearing status was significant for subjective long-term memory complaints and not for subjective short-term memory complaints. Pairwise comparisons, however, revealed no significant differences between hearing loss groups with respect to subjective long-term complaints. Conclusion This cross-sectional study indicates an association between hearing loss and subjective long-term memory complaints but not with subjective short-term memory complaints. In addition, an interaction between hearing status and hearing aid use for subjective long-term memory complaints was observed in hearing-impaired groups, which calls for future research to examine the effects of hearing aid use on different memory systems.